FORMATION OF THE ROOT SYSTEM OF DURUM WHEAT PLANTED AT DIFFERENT PERIODS AND RATES OF RAINFALL (Proceedings of International Educators Conference, 2023)
The article presents the results of the research on the formation of the root system of the durum wheat variety "Mingchinor" under different planting periods and standards under drought conditions. It studied the formation of the root system depending on the biological characteristics of the variety, planting periods, and standards.